Glass and chemically strengthened glass

By adjusting the composition in the glass, the potassium ions diffuse faster than the sodium ions. A simple two-step strengthening treatment is adopted to solve the complicated problems of the three-step strengthening treatment in the prior art, and a significant increase in the depth of the surface compressive stress and compressive stress layer and internal tensile stress suppression are achieved.

CN115776973BActive Publication Date: 2025-05-02AGC INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180048398.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-10
Filing Date
2021-07-05
Publication Date
2025-05-02
Estimated Expiration
2041-07-05

AI Technical Summary

Technical Problem

In the prior art, the three-step strengthening treatment is too complicated, making it difficult to achieve a rough balance between the surface compressive stress and the compressive stress layer with a large depth and suppressing internal tensile stress.

Method used

By adjusting the composition of the glass, the diffusion rate of potassium ions is greater than that of sodium ions. A relatively simple two-step strengthening treatment is adopted, combining ion exchange treatment of sodium ions and potassium ions to form a complex stress distribution.

Benefits of technology

A significant increase in the surface compressive stress and compressive stress layer depth is achieved, while internal tensile stress is suppressed, and a more complex and ideal stress distribution is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115776973B_ABST
    Figure CN115776973B_ABST
Patent Text Reader

Abstract

The present invention relates to a glass having a specific composition range and a parameter M calculated by the following formula of 20 or less. M = -1.15×[SiO2] - 1.73×[Al2O3] + 0.155×[Li2O] + 0.74×[Na2O] - 4.75×[K2O] - 2.1×[B2O3] - 2.17×[P2O5] + 3.25×[MgO] - 2.0×[ZnO] - 13.3×[ZrO2] - 0.80×[Y2O3] + 120.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to glass and chemically strengthened glass. Background Art

[0002] In recent years, cover glass including chemically strengthened glass has been used to protect display devices such as mobile phones, smartphones, and tablet terminals and to improve their appearance.

[0003] In chemically strengthened glass, the greater the surface compressive stress (value) (CS) and the depth of the compressive stress layer (DOL), the higher the strength tends to be. On the other hand, in order to maintain a balance with the surface compressive stress, internal tensile stress (CT) is generated inside the glass, so the greater the CS and DOL, the greater the CT. When glass with a large CT breaks, the number of fragments increases, and the risk of fragments flying becomes greater.

[0004] Patent Document 1 describes that a stress distribution represented by a curved line is formed by a two-step chemical strengthening treatment, thereby enabling the surface compressive stress (CS) to be increased while suppressing the internal tensile stress (CT).

[0005] Patent Document 2 discloses lithium aluminosilicate glass that can obtain relatively large surface compressive stress and compressive stress layer depth by two-step chemical strengthening treatment. Lithium aluminosilicate glass can increase CS and DOL while suppressing CT by two-step chemical strengthening treatment using sodium salt and potassium salt.

[0006] The two-step strengthening treatment usually combines the following treatments: a treatment for forming a compressive stress layer with a relatively small but deep surface compressive stress value by ion exchange between sodium ions with a relatively small ionic radius and lithium ions in the glass; and a treatment for forming a large compressive stress near the surface by ion exchange between potassium ions with a relatively large ionic radius and sodium ions in the glass.

[0007] Patent Document 3 describes that a more complex stress distribution can be formed by three-step chemical strengthening.

[0008] This technology can be said to be a technology that, in addition to the usual two-step chemical strengthening, also performs a process of pulling back alkali ions with large ion radius in the glass by ion exchange with alkali ions with small ion radius, or relaxes the stress generated in the glass by heat treatment, thereby reducing the internal tensile stress CT while further increasing CS and DOL.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: U.S. Patent Application Publication No. 2015 / 0259244

[0012] Patent Document 2: Japanese Patent Application No. 2013-520388

[0013] Patent Document 3: Japanese Patent Application No. 2019-517985 Summary of the invention

[0014] Problems to be solved by the invention

[0015] However, the three-step strengthening process is complicated. An object of the present invention is to provide a chemically strengthened glass having large CS and DOL and suppressed CT by a relatively simple strengthening process. Another object of the present invention is to provide a chemically strengthened glass having large CS and DOL and suppressed CT by a relatively simple strengthening process.

[0016] Means used to solve problems

[0017] Potassium ions with large ionic radius have a slow diffusion rate in glass compared to sodium ions with small ionic radius, so when potassium ions are used for ion exchange treatment, DOL usually becomes smaller. However, the inventors have found that by adjusting the glass composition, the diffusion rate of potassium ions can sometimes be made larger than the diffusion rate of sodium ions. When glass with such a composition is used for ion exchange treatment, a stress distribution different from the past can be formed. Thus, it is believed that a more complex stress distribution in which CS and DOL are larger than in the past and CT is suppressed can be obtained by a relatively simple two-step strengthening process, thereby completing the present invention.

[0018] The present invention provides a glass, wherein, in terms of molar percentage based on oxides, the glass contains:

[0019] 52%~70% SiO2,

[0020] 14% to 25% Al2O3,

[0021] 10% to 18% Li2O,

[0022] 1% to 7% Na2O,

[0023] 0.1%~5% K2O,

[0024] 0~10% B2O3,

[0025] 0~5% P2O5,

[0026] 0~5% MgO,

[0027] 0~5% ZnO,

[0028] 0~2% ZrO2, and

[0029] 0~5% Y2O3, and

[0030] The parameter M obtained by the following formula from the contents of SiO2, Al2O3, Li2O, Na2O, K2O, B2O3, P2O5, MgO, ZnO, ZrO2, and Y2O3 in mol % [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3] is 20 or less,

[0031] M=-1.15×[SiO2]-1.73×[Al2O3]+0.155×[Li2O]+0.74×[Na2O]-4.75×[K2O]-2.1 ×[B2O3]-2.17×[P2O5]+3.25×[MgO]-2.0×[ZnO]-13.3×[ZrO2]-0.80×[Y2O3]+120

[0032] The parameter D of the glass of the present invention, which is obtained by the following formula from [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3], is preferably greater than 1200.

[0033] D=-943×[SiO2]-859×[Al2O3]-998×[Li2O]-991×[Na2O]-1013×[K2O]-949×[ B2O3]-941×[P2O5]-687×[MgO]-956×[ZnO]-1516×[ZrO2]-823×[Y2O3]+95174

[0034] The glass of the present invention is composed of [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3], and the parameter E calculated according to the following formula is preferably greater than 500.

[0035] E=539×[SiO2]+527×[Al2O3]+587×[Li2O]+467×[Na2O]+578×[K2O]+510×[B 2O3]+516×[P2O5]+442×[MgO]+502×[ZnO]+850×[ZrO2]+546×[Y2O3]-53476.

[0036] The present invention provides a glass, wherein, in terms of molar percentage based on oxides, the glass contains:

[0037] 52%~70% SiO2,

[0038] 14% to 25% Al2O3,

[0039] 10% to 18% Li2O,

[0040] 1% to 7% Na2O, and

[0041] 0.1% to 5% K2O,

[0042] When the glass having a thickness of 700 μm is immersed in NaNO 3 at 380° C. for 4 hours, the surface compressive stress value CS0(Na) generated is 500 MPa or more.

[0043] When the glass having a thickness of 700 μm is immersed in KNO3 at 380°C for 4 hours, the surface compressive stress value CS0(K) generated is 1200 MPa or more.

[0044] When the glass having a thickness of 700 μm is immersed in KNO3 at 380°C for 4 hours, the depth of the compressive stress layer DOL(K) generated is 3 μm or more, and

[0045] When the glass having a thickness of 700 μm is immersed in NaNO 3 at 380° C. for 4 hours, the ratio DOL(Na) / DOL(K) of the depth of the compressive stress layer generated to the DOL(K) is 35 or less.

[0046] The compressive stress value CS at a depth of 50 μm from the surface of the glass of the present invention generated when the glass having a thickness of 700 μm is immersed in NaNO3 at 380°C for 4 hours is 50 (Na) is preferably 170 MPa or more.

[0047] The devitrification temperature of the glass of the present invention is preferably 1350° C. or lower.

[0048] The viscosity of the glass of the present invention reaches 10 2 The temperature T2 at dPa·s is preferably 1750° C. or lower.

[0049] The temperature of the DSC exothermic peak of the glass of the present invention measured by the following test method is preferably higher than the glass transition temperature by 150° C. or more.

[0050] (Test method)

[0051] About 70 mg of glass was pulverized and ground with an agate mortar, and measured from room temperature to 1200° C. using a differential scanning calorimeter (DSC) at a heating rate of 10° C. / min.

[0052] The S value represented by the following formula of the glass of the present invention is preferably 0.4 or less.

[0053] S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K )

[0054] Here,

[0055] P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O])

[0056] P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O])

[0057] P K =[K2O] / ([Li2O]+[Na2O]+[K2O])

[0058] Here, [Li2O], [Na2O], and [K2O] represent the contents of Li2O, Na2O, and K2O in mole percentage, respectively.

[0059] The present invention provides a chemically strengthened glass, wherein the chemically strengthened glass is a chemically strengthened glass having a surface compressive stress value of 400 MPa or more, wherein:

[0060] When the Na2O concentration distribution is obtained in the depth direction from the surface to the center of the plate thickness, the depth at which the Na2O concentration reaches the maximum is 1 μm or more, and

[0061] The basic composition of the chemically strengthened glass comprises, in terms of molar percentage based on oxides:

[0062] 52%~70% SiO2,

[0063] 14% to 25% Al2O3,

[0064] 10% to 18% Li2O,

[0065] 1% to 7% Na2O, and

[0066] 0.1%~5% K2O.

[0067] The compressive stress value CS of the chemically strengthened glass of the present invention at a depth of 50 μm from the surface is 50 It is preferably 90 MPa or more.

[0068] The internal tensile stress value CT of the chemically strengthened glass of the present invention is preferably 70.6 MPa or less.

[0069] The surface compressive stress value CS0 of the chemically strengthened glass of the present invention is preferably 800 MPa or more.

[0070] The frequency hopping of the chemically strengthened glass of the present invention is preferably 10 2.5 above.

[0071] Effects of the Invention

[0072] According to the present invention, a chemically strengthened glass having a complex stress distribution with large CS and DOL and suppressed CT can be obtained through a relatively simple strengthening process. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 This is a diagram showing an example of stress distribution of the chemically strengthened glass according to the embodiment of the present invention.

[0074] Figure 2 This is a diagram showing an example of stress distribution of the chemically strengthened glass according to the embodiment of the present invention.

[0075] Figure 3 A diagram showing an electrode pattern used for measuring frequency hopping. DETAILED DESCRIPTION

[0076] Hereinafter, the glass according to the embodiment of the present invention will be described in detail, but the present invention is not limited to the following embodiment and can be implemented with arbitrary modifications within the scope not departing from the gist of the present invention.

[0077] In this specification, "chemically strengthened glass" refers to glass that has been subjected to a chemical strengthening treatment. In addition, "glass for chemical strengthening" refers to glass before being subjected to a chemical strengthening treatment.

[0078] In this specification, the glass composition of chemically strengthened glass is sometimes referred to as the basic composition of chemically strengthened glass. In chemically strengthened glass, a compressive stress layer caused by ion exchange is usually formed on the surface of the glass, so the glass composition of the part where ion exchange is not performed is consistent with the basic composition of chemically strengthened glass. In chemically strengthened glass, except for the case where an extreme ion exchange treatment is performed, the glass composition at a depth of 1 / 2 of the plate thickness t is the basic composition of chemically strengthened glass.

[0079] In this specification, glass composition is expressed as molar percentage based on oxides, and molar % may be expressed simply as %. In addition, “to” expressing a numerical range is used to mean that the numerical values ​​described before and after it are included as the lower limit and the upper limit.

[0080] In the glass composition, “substantially containing no impurities” means that no impurities are contained except inevitable impurities contained in raw materials, etc., that is, no impurities are contained intentionally. Specifically, the content of components other than coloring components is, for example, less than 0.1 mol%.

[0081] In this specification, "stress distribution" is a graph showing the value of compressive stress with the depth from the glass surface as a variable. Negative compressive stress values ​​represent tensile stress.

[0082] In this specification, the property that glass fragments are easily scattered when broken may be referred to as "fragility".

[0083] In this specification, the "stress distribution" can be measured by a method of using an optical waveguide surface strain gauge and a scattered light photoelastic strain gauge in combination or by a method of using a scattered light photoelastic strain gauge.

[0084] It is known that an optical waveguide surface stress gauge can accurately measure the stress of glass in a short time. As an optical waveguide surface stress gauge, there is, for example, FSM-6000 manufactured by Orihara Manufacturing Co., Ltd. However, in principle, an optical waveguide surface stress gauge can only measure stress when the refractive index decreases from the surface of the sample to the inside. In chemically strengthened glass, the refractive index of the layer obtained by replacing the sodium ions inside the glass with potassium ions outside decreases from the surface of the sample to the inside, so the stress can be measured using an optical waveguide surface stress gauge. However, the stress of the layer obtained by replacing the lithium ions inside the glass with sodium ions outside cannot be accurately measured using an optical waveguide surface stress gauge.

[0085] The method using a scattered light photoelastic stress meter can measure stress regardless of the refractive index distribution. As scattered light photoelastic stress meters, for example, there are SLP-1000 and SLP-2000 manufactured by Orihara Manufacturing Co., Ltd. However, the scattered light photoelastic stress meter is easily affected by surface scattering and sometimes cannot accurately measure the stress near the surface. By combining the two measuring devices, accurate stress measurement can be performed.

[0086] <Glass>

[0087] The glass according to the embodiment of the present invention (hereinafter sometimes referred to as "the present glass") is easy to chemically strengthen because the diffusion depth of K ions caused by ion exchange between K ions intruding from the glass surface and Na ions in the glass is relatively deep. In addition, the present glass is suitable for chemically strengthened glass because it is easy to obtain appropriate stress distribution.

[0088] The surface compressive stress value CS0(Na) generated when the present glass having a plate thickness of 700 μm is immersed in NaNO3 at 380°C for 4 hours is preferably 500 MPa or more, more preferably 520 MPa or more, further preferably 550 MPa or more, and particularly preferably 600 MPa or more. When CS0(Na) is above the above value, it is easy to sufficiently increase the compressive stress when the present glass is subjected to a strengthening treatment using sodium ions. In order to prevent severe fracture, CS0(Na) is preferably 1000 MPa or less, more preferably 800 MPa or less. It should be noted that, herein, "the present glass having a plate thickness of 700 μm" refers to "the present glass when the plate thickness is set to 700 μm". That is, according to such a record, there is no restriction on the shape and thickness of the present glass. The specific preferred shape and thickness of the present glass will be described in detail later.

[0089] The surface compressive stress CS0(K) generated when the present glass having a plate thickness of 700 μm is immersed in KNO3 at 380°C for 4 hours is preferably 1200 MPa or more, more preferably 1230 MPa or more, and further preferably 1250 MPa or more. When CS0(K) is above the above value, it is easy to fully increase the compressive stress when strengthening treatment using potassium ions is performed in the present glass. In order to prevent severe fracture, CS0(K) is preferably 1800 MPa or less, and more preferably 1600 MPa or less.

[0090] The compressive stress layer depth DOL(K) generated when the present glass having a plate thickness of 700 μm is immersed in KNO3 at 380°C for 4 hours is preferably 3 μm or more, more preferably 5 μm or more, and further preferably 6.5 μm or more. When DOL(K) is above the above value, the diffusion depth of potassium ions when the present glass is chemically strengthened is easily of sufficient size. From the viewpoint of the ease of designing stress distribution, DOL(K) is preferably 18 μm or less, more preferably 16 μm or less.

[0091] The ratio DOL(Na) / DOL(K) of the depth of the compressive stress layer DOL(Na) generated when the present glass having a thickness of 700 μm is immersed in NaNO3 at 380°C for 4 hours to the above-mentioned DOL(K) is preferably 35 or less, more preferably 30 or less, further preferably 25 or less, further preferably 20 or less, particularly preferably 18 or less, further particularly preferably 17 or less, further preferably 16 or less, and most preferably 15 or less. When DOL(Na) / DOL(K) is below the above-mentioned value, the diffusion rate of potassium ions becomes relatively large relative to the diffusion rate of sodium ions during chemical strengthening, and the balance becomes good, so it is easy to obtain a complex stress distribution. From the viewpoint of increasing the diffusion of sodium ions, DOL(Na) / DOL(K) is preferably 5 or more, more preferably 7 or more, and particularly preferably 8 or more.

[0092] The compressive stress value CS at a depth of 50 μm from the surface generated when the present glass with a plate thickness of 700 μm is immersed in NaNO3 at 380°C for 4 hours is 50 (Na) is preferably 170 MPa or more, more preferably 190 MPa or more, and even more preferably 200 MPa or more. 50 (Na) is within the above range, when the glass is chemically strengthened, it is easy to increase the compressive stress inside the glass and improve the strength. In order to prevent severe fracture, CS 50 (Na) is preferably 500 MPa or less, more preferably 400 MPa or less.

[0093] The compressive stress value CS at a depth of 90 μm from the surface generated when the present glass with a plate thickness of 700 μm is immersed in NaNO3 at 380°C for 4 hours is 90 (Na) is preferably 0 MPa or more, more preferably 0.5 MPa or more, further preferably 5 MPa or more, further preferably 10 MPa or more, and particularly preferably 15 MPa or more. 90 (Na) is within the above range, when the glass is chemically strengthened, it is easy to increase the compressive stress inside the glass and improve the strength. In order to prevent severe fracture, CS 90 (Na) is preferably 200 MPa or less, more preferably 150 MPa or less, and further preferably 100 MPa or less.

[0094] The glass is lithium aluminum silicate glass.

[0095] Specifically, the present glass preferably contains, in terms of molar percentage based on oxides:

[0096] 52%~70% SiO2,

[0097] 14% to 25% Al2O3, and

[0098] 10%~18%Li2O.

[0099] In addition, the present glass preferably contains:

[0100] 1% to 7% Na2O,

[0101] 0.1%~5% K2O,

[0102] 0~10% B2O3,

[0103] 0~5% P2O5,

[0104] 0~5% MgO,

[0105] 0~5% ZnO,

[0106] 0~2% ZrO2, and

[0107] 0~5% Y2O3.

[0108] The content of SiO2, Al2O3, Li2O, Na2O, K2O, B2O3, P2O5, MgO, ZnO, ZrO2, and Y2O3 in the present glass in terms of mole percentage is preferably a parameter M of 20 or less as determined by the following formula [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3]. The value of M is more preferably 18 or less, further preferably 17 or less, particularly preferably 16 or less, further particularly preferably 15 or less, further preferably 13 or less, and most preferably 11 or less.

[0109] M=-1.15×[SiO2]-1.73×[Al2O3]+0.155×[Li2O]+0.74×[Na2O]-4.75×[K2O]-2.1 ×[B2O3]-2.17×[P2O5]+3.25×[MgO]-2.0×[ZnO]-13.3×[ZrO2]-0.80×[Y2O3]+120

[0110] M is a parameter related to the ratio of the diffusion rate of Na ions to the diffusion rate of K ions. When the value of M is within the above range, the ratio of the diffusion rate of Na ions to the diffusion rate of K ions tends to decrease. In order to increase the compressive stress value CS at a depth of 50 μm from the surface, 50 The value of parameter M is preferably greater than 2, more preferably greater than 5, and further preferably greater than 7.

[0111] In addition, the present glass has a composition suitable for chemical strengthening by having the above-mentioned preferred composition range and the parameter M being 20 or less, and the ratio of the diffusion rate of Na ions to the diffusion rate of K ions is adjusted to be within an appropriate range. Thus, a chemically strengthened glass having large CS and DOL and suppressed CT can be easily obtained by a relatively simple strengthening treatment.

[0112] The parameter D obtained by the following formula is preferably not less than 1200. The value of D is more preferably not less than 1230, further preferably not less than 1250, particularly preferably not less than 1300, further preferably not less than 1350, and most preferably not less than 1450.

[0113] D=-943×[SiO2]-859×[Al2O3]-998×[Li2O]-991×[Na2O]-1013×[K2O]-949×[ B2O3]-941×[P2O5]-687×[MgO]-956×[ZnO]-1516×[ZrO2]-823×[Y2O3]+95174

[0114] D is a parameter related to the compressive stress value generated by K ion diffusion. When the value of D is within the above range, there is a tendency for the diffusion rate of K ions to increase. In order to reduce CT, the value of D is preferably 1950 or less, more preferably 1800 or less, and further preferably 1600 or less.

[0115] The parameter E obtained from [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3] according to the following formula is preferably 500 or more. The value of parameter E is more preferably 520 or more, further preferably 550 or more, particularly preferably 570 or more, further preferably 600 or more, and most preferably 650 or more.

[0116] E=539×[SiO2]+527×[Al2O3]+587×[Li2O]+467×[Na2O]+578×[K2O]+510×[B 2O3]+516×[P2O5]+442×[MgO]+502×[ZnO]+850×[ZrO2]+546×[Y2O3]-53476

[0117] E is a parameter related to the compressive stress value generated by the diffusion of Na ions. When the value of E is within the above range, the diffusion rate of Na ions tends to decrease. In order to reduce CT, the value of E is preferably 1000 or less, and more preferably 800 or less.

[0118] Hereinafter, a preferred glass composition will be described.

[0119] SiO2 is a component constituting a network of glass. In addition, SiO2 is a component that improves chemical durability and is a component that reduces cracks generated when damage occurs on the glass surface.

[0120] In order to improve chemical durability, the content of SiO2 is preferably 52% or more, more preferably 56% or more, further preferably 60% or more, further preferably 63% or more, and particularly preferably 65% ​​or more. In order to improve the melting property during glass manufacturing, the content of SiO2 is preferably 70% or less, more preferably 68% or less, and further preferably 65% ​​or less.

[0121] From the viewpoint of improving the ion exchange performance during chemical strengthening and increasing the surface compressive stress after strengthening, Al2O3 is an effective component.

[0122] In order to improve chemical durability and chemical strengthening properties, the content of Al2O3 is preferably 14% or more, more preferably 16% or more, further preferably 18% or more, and particularly preferably 20% or more. On the other hand, when the content of Al2O3 is too much, crystals sometimes grow easily in the melt. In order to prevent the reduction of yield due to devitrification defects, the content of Al2O3 is preferably 25% or less, more preferably 23% or less, and further preferably 21% or less.

[0123] Both SiO2 and Al2O3 are components that stabilize the structure of glass. In order to reduce brittleness, the total content of SiO2 and Al2O3 is preferably 75% or more, more preferably 77% or more, and further preferably 79% or more.

[0124] Both SiO2 and Al2O3 tend to increase the melting temperature of glass. Therefore, in order to make glass melt easily, the total content of SiO2 and Al2O3 is preferably 90% or less, more preferably 87% or less, further preferably 85% or less, and particularly preferably 82% or less.

[0125] Li2O is a component that forms surface compressive stress through ion exchange and is a component that improves the solubility of glass. By making chemically strengthened glass (chemically strengthened glass) contain Li2O, the Li ions on the glass surface are ion-exchanged with Na ions, and the Na ions are further ion-exchanged with K ions, a stress distribution with large surface compressive stress and compressive stress layer can be obtained.

[0126] In order to increase the surface compressive stress during chemical strengthening, the content of Li2O is preferably 10% or more, more preferably 11% or more, further preferably 13% or more, and particularly preferably 15% or more.

[0127] On the other hand, when the content of Li2O is too high, the crystal growth rate during glass molding increases, and the problem of reduced yield due to devitrification defects sometimes increases. In order to suppress devitrification in the glass manufacturing process, the content of Li2O is preferably 18% or less, more preferably 16% or less, further preferably 14% or less, and particularly preferably 12% or less.

[0128] Na2O and K2O are not essential, but both Na2O and K2O are components that improve the solubility of glass and reduce the crystal growth rate of glass. In order to improve the ion exchange performance, the present glass preferably contains at least one of Na2O and K2O.

[0129] Na2O is a component that forms a surface compressive stress layer in a chemical strengthening treatment using potassium salt, and is a component that can improve the solubility of glass. In order to obtain this effect, the content of Na2O is preferably 1% or more, more preferably 2% or more, and further preferably 3% or more. On the other hand, when the content of Na2O is too much, it is difficult to increase the compressive stress of the portion deeper from the surface by chemical strengthening. From such a viewpoint, the content is preferably 7% or less, more preferably 5% or less, and further preferably 3% or less.

[0130] In order to suppress devitrification in the glass manufacturing process, the present glass may contain K2O. When K2O is contained in the present glass, the content of K2O is preferably 0.1% or more, more preferably 0.15% or more, and particularly preferably 0.2% or more. In order to further prevent devitrification, the content of K2O is preferably 0.5% or more, more preferably 1.2% or more. On the other hand, if the glass contains a large amount of K, it sometimes becomes the main cause of the reduction of surface stress due to brittleness and reverse exchange during strengthening. From such a point of view, the content of K2O is preferably 5% or less, more preferably 3% or less, further preferably 1% or less, and particularly preferably 0.5% or less.

[0131] In order to improve the melting property of glass, the total content of Na2O and K2O ([Na2O] + [K2O]) is preferably 3% or more, more preferably 3.5% or more, further preferably 4% or more, and particularly preferably 4.5% or more. When ([Na2O] + [K2O]) is too much, the surface compressive stress value is likely to decrease, so ([Na2O] + [K2O]) is preferably 10% or less, more preferably 8% or less, further preferably 7% or less, and particularly preferably 6% or less.

[0132] In addition, the content of Na2O is preferably larger than that of K2O. This is because K2O tends to increase the surface resistivity.

[0133] In order to reduce the surface resistivity, the ratio of Li2O content to the total content of Li2O, Na2O and K2O is P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O]) is preferably 0.4 or more, more preferably 0.5 or more, and even more preferably 0.6 or more. On the other hand, in order to suppress devitrification during glass melting, P Li It is preferably 0.9 or less, and particularly preferably 0.8 or less.

[0134] In order to suppress devitrification, the ratio of the content of Na2O to the total content of Li2O, Na2O and K2O is P Na=[Na2O] / ([Li2O]+[Na2O]+[K2O]) is preferably 0.1 or more, more preferably 0.2 or more. In order to reduce the surface resistivity, P Na It is preferably 0.5 or less, and more preferably 0.4 or less.

[0135] In order to reduce the surface resistivity, the ratio of K2O content to the total content of Li2O, Na2O and K2O is P K =[K2O] / ([Li2O]+[Na2O]+[K2O]) is preferably 0.3 or less, more preferably 0.2 or less.

[0136] The parameter S value represented by the following formula is preferably 0.4 or less, more preferably 0.37 or less, further preferably 0.35 or less, and particularly preferably 0.34 or less.

[0137] S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K )

[0138] The smaller the parameter S value is, the more biased the content of Li2O, Na2O and K2O is. The smaller the S value is, the more the conductivity of the glass tends to become good and the surface resistivity tends to decrease. From the viewpoint of easy ion exchange, the S value is preferably 0.15 or more, more preferably 0.2 or more.

[0139] MgO, CaO, SrO, BaO and ZnO are not essential, but from the viewpoint of improving the stability of the glass, the present glass may contain any one or more of these substances. When the present glass contains any one or more of MgO, CaO, SrO, BaO and ZnO, the total content [MgO] + [CaO] + [SrO] + [BaO] + [ZnO] is preferably 0.1% or more, more preferably 0.2% or more. In order to maintain a high CS, the total content of these substances is preferably 5% or less, preferably 2% or less, more preferably 1.5% or less, and further preferably 1% or less.

[0140] The present glass may contain MgO in order to reduce viscosity during melting, etc. When the present glass contains MgO, the content of MgO is preferably 1% or more, more preferably 2% or more, and further preferably 3% or more. On the other hand, when the content of MgO is too high, it is difficult to increase the compressive stress value during chemical strengthening treatment. The content of MgO is preferably 5% or less, more preferably 4% or less, further preferably 3% or less, and particularly preferably 2% or less.

[0141] CaO is a component that improves the meltability of glass. The present glass may contain CaO. When the present glass contains CaO, the content of CaO is preferably 0.1% or more, more preferably 0.15% or more, and further preferably 0.5% or more. On the other hand, when the content of CaO is excessive, it is difficult to increase the compressive stress value during chemical strengthening treatment. The content of CaO is preferably 5% or less, more preferably 3% or less, further preferably 1% or less, and typically 0.5% or less.

[0142] ZnO is a component that improves the solubility of glass. The present glass may contain ZnO. When the present glass contains ZnO, the content of ZnO is preferably 0.2% or more, more preferably 0.5% or more. In order to improve the weather resistance of the glass, the content of ZnO is preferably 5% or less, more preferably 3% or less, and further preferably less than 1%.

[0143] ZnO, SrO and BaO tend to deteriorate the chemical strengthening properties. In order to facilitate chemical strengthening of the glass, the total content of [ZnO]+[SrO]+[BaO] is preferably 3% or less, more preferably less than 1%, and further preferably 0.5% or less. It is particularly preferred that ZnO, SrO and BaO are substantially absent.

[0144] The present glass may not contain ZrO2. On the other hand, from the viewpoint of increasing the surface compressive stress of the chemically strengthened glass, the present glass preferably contains ZrO2. The content of ZrO2 is preferably 0.1% or more, more preferably 0.15% or more, further preferably 0.2% or more, particularly preferably 0.25% or more, and further preferably 0.3% or more. On the other hand, when the content of ZrO2 is too high, devitrification defects are likely to occur, and it is difficult to increase the compressive stress value during chemical strengthening treatment. The content of ZrO2 is preferably 2% or less, more preferably 1.5% or less, further preferably 1% or less, and particularly preferably 0.8% or less.

[0145] In order to increase the fracture toughness value, the present glass preferably contains a total of 0.2% or more of any one or more of Y2O3, La2O3 and ZrO2. The total content of Y2O3, La2O3 and ZrO2 is preferably 0.5% or more, more preferably 1.0% or more, and further preferably 1.5% or more. In addition, in order to lower the liquidus temperature and suppress devitrification, their total content is preferably 6% or less, more preferably 5% or less, and further preferably 4% or less.

[0146] In order to lower the devitrification temperature and suppress devitrification, the total content of Y2O3 and La2O3 is preferably greater than the content of ZrO2, and the content of Y2O3 is more preferably greater than the content of ZrO2.

[0147] Y2O3 is not essential, but in order to increase the surface compressive stress of the chemically strengthened glass and reduce the crystal growth rate, the present glass preferably contains Y2O3.

[0148] When the present glass contains Y2O3, the content of Y2O3 is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.5% or more, and particularly preferably 1% or more. On the other hand, when Y2O3 is too much, it is difficult to increase the compressive stress value during chemical strengthening treatment. The content of Y2O3 is preferably 5% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1.5% or less.

[0149] La2O3 is not essential, but the present glass may contain La2O3 for the same reason as Y2O3. When the present glass contains La2O3, the content of La2O3 is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.5% or more, and particularly preferably 0.8% or more. On the other hand, when La2O3 is excessive, it is difficult to increase the compressive stress value during chemical strengthening treatment. The content of La2O3 is preferably 5% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1.5% or less.

[0150] TiO2 is used to inhibit the sun exposure of glass ( ) component. The present glass may contain TiO2. When the present glass contains TiO2, the content of TiO2 is preferably 0.02% or more, more preferably 0.03% or more, further preferably 0.04% or more, particularly preferably 0.05% or more, further preferably 0.06% or more. On the other hand, when the content of TiO2 is greater than 1%, devitrification is likely to occur, and the quality of the chemically strengthened glass may be reduced. The content of TiO2 is preferably 1% or less, more preferably 0.5% or less, further preferably 0.25% or less.

[0151] B2O3 is not indispensable, but the present glass may contain B2O3 for the purpose of reducing the brittleness of the glass and improving the crack resistance or for the purpose of improving the solubility of the glass. When the present glass contains B2O3, the content of B2O3 is preferably 0.5% or more, preferably 1% or more, and more preferably 2% or more. On the other hand, when the content of B2O3 is too much, the acid resistance tends to deteriorate. The content of B2O3 is preferably 10% or less. The content of B2O3 is more preferably 6% or less, more preferably 4% or less, and particularly preferably 2% or less. From the viewpoint of preventing the problem of wave streaks during melting, the present glass is more preferably substantially free of B2O3.

[0152] P2O5 is not essential, but the present glass may contain P2O5 for the purpose of increasing the compressive stress value during chemical strengthening. When the present glass contains P2O5, the content of P2O5 is preferably 0.5% or more, preferably 1% or more, and more preferably 2% or more. On the other hand, from the viewpoint of improving acid resistance, the content of P2O5 is preferably 5% or less, more preferably 4% or less, and more preferably 2% or less. From the viewpoint of preventing the generation of ribs during melting, the present glass more preferably contains substantially no P2O5.

[0153] The total content of B2O3 and P2O5 is preferably 0 to 10%, more preferably 1% or more, and further preferably 2% or more. The total content of B2O3 and P2O5 is more preferably 6% or less, and further preferably 4% or less.

[0154] Nb2O5, Ta2O5, Gd2O3 and CeO2 are components that inhibit the sunlight of the glass and are components that improve the solubility. The present glass may contain at least one or more of Nb2O5, Ta2O5, Gd2O3 and CeO2. When the present glass contains these components, the total content is preferably 0.03% or more, more preferably 0.1% or more, further preferably 0.5% or more, particularly preferably 0.8% or more, and further preferably 1% or more. On the other hand, when their content is too much, it is difficult to increase the compressive stress value during chemical strengthening treatment, so the total content is preferably 3% or less, more preferably 2% or less, further preferably 1% or less, and particularly preferably 0.5% or less.

[0155] Fe2O3 absorbs heat rays and thus has the effect of improving the solubility of glass. When glass is mass-produced using a large melting furnace, the present glass preferably contains Fe2O3. In this case, the content of Fe2O3 is preferably 0.002% or more, more preferably 0.005% or more, further preferably 0.007% or more, and particularly preferably 0.01% or more, based on the weight % of the oxide. On the other hand, when Fe2O3 is contained in excess, coloring occurs. Therefore, from the viewpoint of improving the transparency of the glass, its content is preferably 0.3% or less, more preferably 0.04% or less, further preferably 0.025% or less, and particularly preferably 0.015% or less, based on the weight % of the oxide.

[0156] It should be noted that all iron oxides in the glass are described here in the form of Fe2O3, but in fact, oxidized Fe(III) and reduced Fe(II) are usually present in a mixture. Among them, Fe(III) produces yellow coloration, Fe(II) produces blue coloration, and the glass produces green coloration under the balance of the two.

[0157] In addition, the present glass may contain coloring components within a range that does not hinder the desired chemical strengthening properties. As coloring components, for example, Co3O4, MnO2, NiO, CuO, Cr2O3, V2O5, Bi2O3, SeO2, CeO2, Er2O3, Nd2O3, etc. can be listed as appropriate coloring components.

[0158] The content of the coloring components is preferably 5% or less in total in terms of molar percentage based on the oxide. When it is greater than 5%, the glass may be easily devitrified. The content of the coloring components is preferably 3% or less, and more preferably 1% or less. In the case of increasing the transmittance of the glass, it is preferred that these components are substantially absent.

[0159] The present glass may contain sulfates, chlorides, fluorides, etc. as a clarifier for glass melting. The present glass preferably does not contain As2O3. When the present glass contains Sb2O3, its content is preferably 0.3% or less, more preferably 0.1% or less, and most preferably not contained.

[0160] The fracture toughness value of the present glass is preferably 0.70 MPa·m 1 / 2 More preferably, 0.75 MPa·m 1 / 2 More preferably, 0.80 MPa·m 1 / 2 Above, particularly preferably 0.83 MPa·m 1 / 2 In addition, the fracture toughness value is usually 2.0MPa·m 1 / 2 Below, typically 1.5 MPa·m 1 / 2 Due to the high fracture toughness value, even if a large surface compressive stress is introduced into the glass by chemical strengthening, it is not easy to cause severe breakage.

[0161] The fracture toughness value can be measured, for example, using the DCDC method (Acta metall. mater. Vol. 43, pp. 3453-3458, 1995).

[0162] In order to make the glass less prone to breakage, the Young's modulus of the present glass is preferably 80 GPa or more, more preferably 82 GPa or more, further preferably 84 GPa or more, and particularly preferably 85 GPa or more. There is no particular restriction on the upper limit of the Young's modulus, but a glass with a high Young's modulus sometimes has reduced acid resistance, so for example, it is preferably 110 GPa or less, more preferably 100 GPa or less, and further preferably 90 GPa or less. The Young's modulus can be measured, for example, by an ultrasonic pulse method (JIS R1602: 1995).

[0163] From the viewpoint of reducing the warpage after chemical strengthening, the average linear thermal expansion coefficient (thermal expansion coefficient) of the present glass at 50°C to 350°C is preferably 95×10-7 / °C or less, more preferably 90×10 -7 / °C or less, more preferably 88×10 -7 / ℃ or less, particularly preferably 86×10 -7 / ℃ or less, the most preferred is 84×10 -7 / °C or less. There is no particular restriction on the lower limit of the thermal expansion coefficient, but glass with a small thermal expansion coefficient is sometimes difficult to melt. Therefore, the average linear thermal expansion coefficient (thermal expansion coefficient) of the present glass at 50°C to 350°C is preferably, for example, 60×10 -7 / °C or more, more preferably 70×10 -7 / ℃ or more, more preferably 74×10 -7 / ℃ or more, more preferably 76×10 -7 / ℃ or above.

[0164] From the viewpoint of reducing the warpage after chemical strengthening, the glass transition temperature (Tg) is preferably 500°C or higher, more preferably 520°C or higher, and further preferably 540°C or higher. From the viewpoint of facilitating float forming, it is preferably 750°C or lower, more preferably 700°C or lower, further preferably 650°C or lower, particularly preferably 600°C or lower, and most preferably 580°C or lower.

[0165] In the present glass, the temperature of the DSC exothermic peak measured by the following test method is preferably higher than the glass transition temperature by 150° C. or more.

[0166] Specifically, about 70 mg of glass was ground using an agate mortar, and the temperature was measured from room temperature to 1200° C. using a differential scanning calorimeter (DSC) at a heating rate of 10° C. / min.

[0167] The temperature of the DSC exothermic peak is preferably 120°C or higher than Tg, and more preferably 150°C or higher. When the temperature of the DSC exothermic peak is above the above value, crystals are not easily generated when the glass is heated and formed. As a result, for example, 3D molding of the glass becomes easy. The temperature of the DSC exothermic peak is usually below (Tg+300°C), and more preferably below (Tg+250°C).

[0168] Viscosity reaches 10 2The temperature (T2) at 100 dPa·s is preferably 1750°C or less, more preferably 1730°C or less, further preferably 1700°C or less, particularly preferably 1675°C or less, and typically 1650°C or less. The temperature (T2) is a standard temperature for the melting point of glass, and the lower the T2, the easier it is to manufacture the glass. There is no particular restriction on the lower limit of T2, but the glass with a low T2 tends to have an excessively low glass transition temperature, so T2 is usually 1400°C or more, preferably 1450°C or more.

[0169] In addition, the viscosity reaches 10 4 dPa·s, the temperature (T4) is preferably 1350°C or less, more preferably 1300°C or less, further preferably 1250°C or less, and particularly preferably 1150°C or less. The temperature (T4) is a standard temperature for forming glass into a plate shape, and a glass with a high T4 tends to increase the load on the forming equipment. There is no particular restriction on the lower limit of T4, but a glass with a low T4 tends to have an excessively low glass transition temperature, so T4 is usually 900°C or more, preferably 950°C or more, and more preferably 1000°C or more.

[0170] When the devitrification temperature of the glass is 4 When the temperature (T4) at dPa·s is 120°C or lower, devitrification is less likely to occur during the forming by the float process, which is preferred. The devitrification temperature is more preferably 100°C or lower than T4, further preferably 50°C or lower than T4, and particularly preferably lower than T4. For example, when T4 is 1230°C, the devitrification temperature is preferably 1350°C or lower, more preferably 1330°C or lower, and further preferably 1280°C or lower.

[0171] In view of ease of production, the devitrification growth rate of the present glass is preferably 10000 μm / hour or less, more preferably 8000 μm / hour or less. The devitrification growth rate refers to the growth rate of crystals generated by the devitrification phenomenon, and can be measured by the method described in the Examples, for example.

[0172] The softening point of the present glass is preferably below 850°C, more preferably below 820°C, and further preferably below 790°C. This is because the lower the softening point of the glass, the lower the heat treatment temperature in the bending forming, the lower the energy consumption, and the smaller the load on the equipment. From the viewpoint of reducing the bending forming temperature, the lower the softening point, the more preferred, but it is above 700°C in ordinary glass. Glass with too low a softening point has a tendency to easily relax the stress introduced during the chemical strengthening treatment and easily become low in strength, so the softening point is preferably above 700°C. It is more preferably above 720°C, and further preferably above 740°C. The softening point can be measured by the fiber elongation method described in JIS R3103-1:2001.

[0173] In the present glass, it is preferred that the crystallization peak temperature measured by the following measurement method is higher than the softening point - 100° C. It is more preferred that no crystallization peak is observed.

[0174] Specifically, about 70 mg of glass was pulverized and ground using an agate mortar, and the temperature was measured from room temperature to 1200° C. using a differential scanning calorimeter (DSC) at a heating rate of 10° C. / min.

[0175] In order to reduce the amount of charge on the glass surface, the surface resistivity of the glass at 50°C is preferably 10 15 Ω / sq or less, more preferably 10 14.5 Ω / sq or less, more preferably 10 14 Ω / sq or less. In addition, glass with a small amount of charge tends to have poor devitrification characteristics during production, so the surface resistivity is preferably 10 8 Ω / sq or more, more preferably 10 9 Ω / sq or more. The smaller the surface resistivity, the better the conductivity of the glass. The surface resistivity ρ is obtained by forming an electrode on the surface of the glass plate and measuring the current value I and the voltage V as R=V / I to obtain the resistance value R, and by ρ=R×r from the resistance value R and the electrode coefficient r.

[0176] When the present glass is in the form of a plate (glass plate), from the viewpoint of improving the effect of chemical strengthening, the plate thickness (t) is preferably 2000 μm or less, more preferably 1500 μm or less, further preferably 1000 μm or less, further preferably 900 μm or less, particularly preferably 800 μm or less, and most preferably 700 μm or less. In addition, from the viewpoint of obtaining a sufficient effect of strength improvement by chemical strengthening treatment, the plate thickness is preferably 100 μm or more, more preferably 200 μm or more, further preferably 400 μm or more, and further preferably 500 μm or more.

[0177] The shape of the present glass may be other than a plate shape depending on the applicable product, application, etc. In addition, the glass plate may have a rim shape with different thicknesses on the outer circumference. In addition, the shape of the glass plate is not limited thereto, for example, the two main surfaces may not be parallel to each other, and one or both of the two main surfaces may be a curved surface in whole or in part. More specifically, the glass plate may be, for example, a flat glass plate without warping, or a curved glass plate with a curved surface.

[0178] The glass of the embodiment of the present invention can be manufactured by a common method. For example, the raw materials of each component of the glass are mixed and heated and melted in a glass melting furnace. Then, the glass is homogenized by a known method, formed into a desired shape such as a glass plate, and slowly cooled.

[0179] As the forming method of the glass sheet, for example, the float process, the press process, the fusion process and the down-draw process can be cited. The float process suitable for mass production is particularly preferred. In addition, continuous forming methods other than the float process, such as the fusion process and the down-draw process, are also preferred.

[0180] Then, the formed glass is ground and polished as needed to form a glass substrate. It should be noted that when the glass substrate is cut into a specified shape and size or the glass substrate is chamfered, if the cutting and chamfering of the glass substrate are performed before the chemical strengthening treatment described later, a compressive stress layer is also formed on the end face by the subsequent chemical strengthening treatment, which is preferred.

[0181] <Chemically strengthened glass>

[0182] The basic composition of the chemically strengthened glass according to the embodiment of the present invention (hereinafter, also simply referred to as the present chemically strengthened glass) is the same as the glass composition of the present glass described above. Figure 1 and Figure 2 This is a diagram showing an example of stress distribution of the chemically strengthened glass. Figure 2 This is the stress distribution inside the chemically strengthened glass measured using a scattered light photoelastic stress meter. It should be noted that the interior here refers to, for example, a range of 30 μm or more in depth from the surface.

[0183] The surface compressive stress value CS0 of the present chemically strengthened glass is preferably 400 MPa or more, more preferably 600 MPa or more, further preferably 700 MPa or more, further preferably 800 MPa or more, and particularly preferably 850 MPa or more.

[0184] The greater the surface compressive stress value, the higher the strength. However, when the surface compressive stress value is too large, a large tensile stress is generated inside the chemically strengthened glass, which may cause fracture. Therefore, the surface compressive stress value CS0 is preferably 1600 MPa or less, and more preferably 1500 MPa or less.

[0185] In the stress distribution of the chemically strengthened glass, the compressive stress value CS at a depth of 50 μm from the surface is 50 It is preferably 90 MPa or more, more preferably 110 MPa or more, further preferably 130 MPa or more, further preferably 140 MPa or more, particularly preferably 150 MPa or more, and most preferably 160 MPa or more. 50 The CS is large, so it is not easy to break when the chemically strengthened glass is damaged by falling from a high place. From the perspective of suppressing the generation of large tensile stress inside the chemically strengthened glass and causing fracture, 50 It is preferably 300 MPa or less, more preferably 250 MPa or less, and further preferably 200 MPa or less.

[0186] In the present chemically strengthened glass, the tensile stress value at a depth of 1 / 2 of the plate thickness t of the glass, i.e., the internal tensile stress value CT is preferably 70.6 MPa or less, more preferably 62.1 MPa or less, further preferably 61.8 MPa or less, and further preferably 56.9 MPa or less. The smaller the CT, the less likely it is to break. The internal tensile stress value CT is preferably 50 MPa or more, more preferably 53 MPa or more, and further preferably 55 MPa or more. When the CT is above the above value, the compressive stress near the surface increases and the strength increases.

[0187] When the distribution of Na2O concentration is obtained in the depth direction from the surface to the center of the plate thickness, the depth at which the Na2O concentration of the present chemically strengthened glass reaches the maximum is preferably 0.01t or more.

[0188] The depth at which the Na2O concentration reaches the maximum is preferably 0.025t or more, more preferably 0.045t or more, further preferably 0.055t or more, and particularly preferably 0.0625t or more. In addition, in the case of a normal thickness, the depth at which the Na2O concentration reaches the maximum is preferably 0.15t or less, more preferably 0.1t or less, and further preferably 0.08t or less.

[0189] The depth at which the Na2O concentration reaches the maximum is preferably 1 μm or more, more preferably 10 μm or more, and further preferably 15 μm or more. To prevent breakage caused by strong impact, it is preferably 20 μm or more, more preferably 30 μm or more, and further preferably 40 μm to 60 μm.

[0190] When the depth at which the Na2O concentration reaches the maximum is within the above range, it is easy to obtain glass having a large compressive stress inside the glass while suppressing CT.

[0191] The depth at which the Na2O concentration reaches the maximum can be determined by measuring the concentration distribution in the thickness direction of a cross section of a chemically strengthened glass using an electron probe microanalyzer (EPMA).

[0192] The hopping frequency of the chemically strengthened glass measured by the following method is preferably 10 2.5 More than 10 3.0 More than 10 3.5 When the frequency hopping is too large, the glass may have poor devitrification characteristics or reduced fracture toughness. The frequency hopping is preferably 10 6.0 Below, more preferably 10 5.5 Below, more preferably 10 5.0 the following.

[0193] (Method for measuring frequency hopping)

[0194] The glass plate was processed into a plate shape of 50 mm × 50 mm × 0.7 mm and a Figure 3 The electrode pattern shown.

[0195] The impedance at 20 MHz to 2 MHz was measured using an impedance analyzer to determine the complex admittance.

[0196] Assuming K = -11.214, n1 = 0.995, n2 = 0.576, C∞ = 20.726, the hopping frequency ωp is calculated according to the following formula (13) (Almond-west formula) and the obtained complex admittance.

[0197] It should be noted that the following equation (13) is known as a model formula related to complex admittance Y*(ω) and having frequency ω as a variable (Journal of Materials Science, Vol. 19, 1984: pp. 3236-3248).

[0198]

[0199] Here, A1, B1, A2, and B2 are as follows.

[0200]

[0201] B1=A1tan(n1π / 2) (15)

[0202]

[0203] B2=A2tan(n2π / 2) (17)

[0204] The chemically strengthened glass can be manufactured by subjecting the above-mentioned glass to chemical strengthening treatment, followed by washing and drying. The preferred shape of the chemically strengthened glass is the same as the preferred shape of the glass, and for example, it can be a flat glass plate without warping, a curved glass plate with a curved surface, or a shape other than a plate. In the manufacture of the chemically strengthened glass, the chemical strengthening treatment can be applied to a flat glass plate, and when the chemically strengthened glass is a curved glass plate, the chemical strengthening treatment can be applied to a curved glass plate. In addition, the chemical strengthening treatment can be applied to glass in a shape other than a plate.

[0205] Chemical strengthening treatment can be carried out by a known method. In the chemical strengthening treatment, the glass sheet is contacted with a melt of a metal salt (e.g., potassium nitrate) containing a metal ion with a large ionic radius by immersion or the like. Thus, the metal ions with a small ionic radius in the glass sheet are replaced with metal ions with a large ionic radius. Here, the metal ions with a small ionic radius are typically Na ions or Li ions. The metal ions with a large ionic radius are typically K ions or Na ions, specifically, K ions for Na ions and Na ions or K ions for Li ions.

[0206] The chemical strengthening treatment (ion exchange treatment) can be performed, for example, by immersing the glass plate in a molten salt such as potassium nitrate heated to 360° C. to 600° C. for 0.1 to 500 hours. It should be noted that the heating temperature of the molten salt is preferably 375° C. to 500° C., and the immersion time of the glass plate in the molten salt is preferably 0.3 to 200 hours.

[0207] As molten salts for chemical strengthening treatment, for example, nitrates, sulfates, carbonates, chlorides, etc. can be cited. Among them, as nitrates, for example, lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate and silver nitrate can be cited. As sulfates, for example, lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, silver sulfate, etc. can be cited. As carbonates, for example, lithium carbonate, sodium carbonate and potassium carbonate can be cited. As chlorides, for example, lithium chloride, sodium chloride, potassium chloride, cesium chloride, silver chloride, etc. can be cited. These molten salts can be used alone or in combination.

[0208] In this embodiment, the treatment conditions of the chemical strengthening treatment can be appropriately selected in consideration of the properties and composition of the glass, the type of molten salt, and the chemical strengthening properties such as the desired surface compressive stress and depth of the compressive stress layer of the final chemically strengthened glass.

[0209] In addition, in the present embodiment, the chemical strengthening treatment may be performed only once or multiple chemical strengthening treatments may be performed under two or more different conditions (multi-step strengthening). Here, for example, as the first step of the chemical strengthening treatment, the chemical strengthening treatment is performed under the condition that the DOL is large and the CS is relatively small. Then, as the second step of the chemical strengthening treatment, when the chemical strengthening treatment is performed under the condition that the DOL is small and the CS is relatively high, the CS of the outermost surface of the chemically strengthened glass can be increased, and at the same time, the internal tensile stress area (St) can be suppressed, and the internal tensile stress (CT) can be suppressed to a low level.

[0210] The present glass and the present chemically strengthened glass are particularly useful as protective glass used in mobile devices such as mobile phones, smart phones, portable information terminals (PDAs), and tablet terminals. In addition, they are also useful as protective glass for display devices such as televisions (TVs), personal computers (PCs), and touch panels that are not intended to be carried, building materials such as elevator walls, walls of buildings such as houses or buildings (full-screen displays), window glass, etc., desktops, interiors of cars or airplanes, etc., or protective glass thereof, and in applications such as housings having non-plate-shaped curved surfaces by bending or forming.

[0211] Example

[0212] The present invention is described below by way of examples, but the present invention is not limited thereto. Examples 1 to 13, 21 to 37, and 39 are examples of the present glass, and Examples 14 to 20, 38, and 40 are comparative examples. It should be noted that, for each measurement result in the table, "-" means not evaluated.

[0213] (Production of chemically strengthened glass)

[0214] According to the glass compositions shown in Tables 1 to 3 in terms of molar percentage based on oxides, a glass plate is made by melting in a platinum crucible. Appropriately select commonly used glass raw materials such as oxides, hydroxides, carbonates or nitrates, and weigh them in such a way that 1000g of glass is obtained. Next, the mixed raw materials are placed in a platinum crucible and melted in a resistance-heated electric furnace at 1500°C to 1700°C for about 3 hours, and degassing and homogenization are performed. The obtained molten glass is poured into a mold, kept at a temperature of glass transition temperature + 50°C for 1 hour, and then cooled to room temperature at a rate of 0.5°C / min to obtain a glass block. The obtained glass block is cut and ground, and finally both sides are processed into a mirror surface, thereby obtaining a plate-shaped glass (chemically strengthened glass) with a length of 50mm × a width of 50mm × a thickness of 0.8mm. It should be noted that in Tables 1 to 3, R2O represents the total content of Li2O, K2O and Na2O.

[0215]

[0216]

[0217]

[0218] The physical properties of the obtained chemically strengthened glass were evaluated as follows. The results are shown in Tables 4 to 6. In Tables 4 to 6, the numerical values ​​indicated in bold and italics are values ​​estimated from the glass composition.

[0219] <Density (d)>

[0220] Density measurement is carried out according to the liquid weighing method (JIS z8807:2012 Determination of density and specific gravity of solids). The unit is g / cm 3 .

[0221] <Young's modulus>

[0222] The Young's modulus (G) (unit: GPa) was measured by an ultrasonic pulse method (JIS R1602: 1995).

[0223] <Average Linear Thermal Expansion Coefficient α and Glass Transition Temperature (Tg)>

[0224] Average linear expansion coefficient (α) at ​​a temperature of 50°C to 350°C (unit: 10 -7 The average linear expansion coefficient of glass (°C) and the glass transition temperature (°C) were measured in accordance with JIS R3102:1995 "Test method for average linear expansion coefficient of glass".

[0225] <T2、T4>

[0226] The viscosity was measured by a rotational viscometer (based on ASTM C 965-96) up to 10 2 dPa·s when the temperature T2(℃) and viscosity reach 10 4 dPa·s at temperature T4 (℃).

[0227] <Devitrification growth rate>

[0228] The growth rate of crystals caused by devitrification was measured according to the following procedure.

[0229] The glass pieces were crushed and classified in a mortar, and the glass particles that passed through a sieve with a mesh size of 3.35 mm and did not pass through a sieve with a mesh size of 2.36 mm were washed with ion-exchanged water and dried before use in the test.

[0230] Place a glass particle in each of the recesses of an elongated platinum cell having a plurality of recesses, maintain at 1350 °C or higher for 15 minutes or longer, then take out from the furnace, and heat in an electric furnace at 700 °C to 1300 °C until the surface of the glass particle melts and becomes smooth.

[0231] Next, put the glass into a temperature gradient furnace maintained at a specified temperature, perform heat treatment for a certain period of time (designated as w), then take out to room temperature and perform quenching. According to this method, an elongated container can be set in the temperature gradient furnace, and heat treatment can be performed on a plurality of glass particles simultaneously.

[0232] Observe the heat-treated glass using a polarized light microscope (manufactured by Nikon Corporation: ECLIPSE LV100ND), and measure the diameter of the largest crystal in the observed crystals (designated as L μm). Observation is performed under the conditions of 10 times magnification of the eyepiece, 5 times to 100 times magnification of the objective lens, transmitted light, and polarized light observation. Since it can be considered that the crystals generated by devitrification grow isotropically, the devitrification (crystal) growth rate is (L / 2) / w [unit: μm / hour].

[0233] Among them, the crystals to be measured are selected from the crystals that do not precipitate from the interface with the container. This is because the devitrification growth at the metal interface has a different tendency from the normal devitrification growth behavior occurring inside the glass and at the glass-atmosphere interface.

[0234] <Devitrification temperature>

[0235] Put the crushed glass particles into a platinum dish, and perform heat treatment in an electric furnace controlled at a certain temperature for 17 hours. Observe the heat-treated glass using a polarized light microscope, and estimate the devitrification temperature by the method of evaluating the presence or absence of devitrification. For example, in the table, when it is recorded as "1000 °C - 1025 °C", it means that devitrification occurs when heat treatment is performed at 1000 °C, but does not occur in the treatment at 1025 °C. In this case, the devitrification temperature is greater than or equal to 1000 °C and less than 1025 °C.

[0236] <DSC peak temperature>

[0237] For the DSC peak temperature (°C), crush about 70 mg of glass and grind it using an agate mortar, set the heating rate to 10 °C / minute, and measure from room temperature to 1200 °C using a differential scanning calorimeter (DSC).

[0238] <CS0(Na), CS 50 (Na), CS 90 (Na), DOL(Na)>

[0239] Glass having a thickness of 700 μm was chemically strengthened by immersing it in NaNO 3 at 380° C. for 4 hours.

[0240] For the chemically strengthened glass obtained, the surface compressive stress (value) (CS, DOL) was measured using a surface stress meter (surface stress meter FSM-6000 manufactured by Orihara Seisakusho Co., Ltd.). The internal CS and DOL were measured using a scattered light photoelastic stress meter (SLP-1000 manufactured by Orihara Seisakusho Co., Ltd.). 50 (Na), CS 90 (Na) and DOL (Na) are shown in the table.

[0241] <CS0(K)、DOL(K)>

[0242] Glass having a thickness of 700 μm was chemically strengthened by immersing it in KNO 3 at 380° C. for 4 hours.

[0243] The obtained chemically strengthened glass was measured for CS and DOL in the same manner as in the case of strengthening using NaNO 3. CS0(K) and DOL(K) of each glass are shown in the table.

[0244]

[0245]

[0246]

[0247] <Chemical Strengthening Properties>

[0248] The glass of Example 9 was subjected to two-step chemical strengthening as follows. That is, as the first step of chemical strengthening treatment, it was immersed in a molten salt of 70 wt% KNO3 and 30 wt% NaNO3 at 380°C for 90 minutes. In addition, as the second step of strengthening treatment, it was immersed in a molten salt of 99 wt% KNO3 and 1 wt% LiNO3 at 380°C for 40 minutes.

[0249] The compressive stress value of the surface layer of the obtained chemically strengthened glass was measured using a surface stress meter (FSM-6000), and the CS and DOL of the inside were measured using a scattered light photoelastic stress meter (SLP-1000).

[0250] The CS0 of the obtained chemically strengthened glass is 818 MPa, and the CS 50 The K ion exchange depth was 3.3 μm and the DOL was 104 μm.

[0251] exist Figure 1The stress distribution of the obtained chemically strengthened glass is shown in FIG. Figure 2 The stress distribution inside the chemically strengthened glass measured using a scattered light photoelastic stress meter (SLP-1000) is shown. It should be noted that the inside here refers to a range of 30 μm or more in depth from the surface.

[0252] according to Figure 2 , the peak value of the compressive stress caused by the diffusion of Na ions can be confirmed at a depth of about 33 μm from the surface of the glass. It can be considered that since the depth at which the Na2O concentration reaches the maximum is more than 1 μm, when the Na2O concentration distribution is taken in the depth direction from the surface of the present glass toward the center of the plate thickness, the depth at which the Na2O concentration reaches the maximum is also more than 1 μm.

[0253] The parameter M of the glass of the embodiment is within the preferred range, so the value of DOL(Na) / DOL(K) is small. Therefore, the diffusion rate of potassium ions during chemical strengthening is relatively large compared to the diffusion rate of sodium ions. Therefore, the glass of the embodiment is obtained by a relatively simple strengthening process. Figure 1 The chemically strengthened glass shown has large CS of the compressive stress layer due to diffusion of Na ions at a depth of 50 μm from the surface and large DOL and CS of the compressive stress layer due to diffusion of K ions in the surface layer, and has suppressed CT.

[0254] On the other hand, the glass of the comparative example has a large value of DOL(Na) / DOL(K) as in the conventional example, so it is considered that it is difficult to obtain the complex stress distribution described above by a simple strengthening treatment. Alternatively, the glass of the comparative example has insufficient amounts of Li and Al required to obtain internal and surface compressive stress, resulting in low compressive stress.

[0255] Although the present invention is described in detail and with reference to specific embodiments, various changes and modifications can be applied without departing from the spirit and scope of the present invention, which is obvious to those skilled in the art. This application is based on Japanese patent application (Japanese patent application 2020-119445) filed on July 10, 2020, the contents of which are incorporated herein by reference.

Claims

1. A glass, wherein: The glass contains, in mole percentage based on oxides: 52%~70% SiO2, 14% to 25% Al2O3, 10% to 18% Li2O, 1% to 7% Na2O, 0.1%~5% K2O, 0~10% B2O3, 0~5% P2O5, 0~5% MgO, 0~5% ZnO, 0~0.8% ZrO2, and 0~5% Y2O3, and The parameter M obtained by the following formula from the contents of SiO2, Al2O3, Li2O, Na2O, K2O, B2O3, P2O5, MgO, ZnO, ZrO2, and Y2O3 in mol % [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3] is 2 or more and 20 or less, The parameter D obtained by the following formula from [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3] is greater than 1200. D=-943×[SiO2]-859×[Al2O3]-998×[Li2O]-991×[Na2O]-1013×[K2O] -949×[B2O3]-941×[P2O5]-687×[MgO]-956×[ZnO]-1516×[ZrO2]-823×[Y2O3]+95174, M=-1.15×[SiO2]-1.73×[Al2O3]+0.155×[Li2O]+0.74×[Na2O]-4.75 ×[K2O]-2.1×[B2O3]-2.17×[P2O5]+3.25×[MgO]-2.0×[ZnO]-13.3×[ZrO2]-0.80×[Y2O3]+120, The S value represented by the following formula is 0.34 or less, S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K ) Here, P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O]) P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O]) P K =[K2O] / ([Li2O]+[Na2O]+[K2O]) Here, [Li2O], [Na2O], and [K2O] represent the contents of Li2O, Na2O, and K2O in mole percentage, respectively.

2. The glass according to claim 1, wherein: The parameter E obtained by the following formula from [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3] is greater than 500. E=539×[SiO2]+527×[Al2O3]+587×[Li2O]+467×[Na2O]+578×[K2O]+ 510×[B2O3]+516×[P2O5]+442×[MgO]+502×[ZnO]+850×[ZrO2]+546×[Y2O3]-53476.

3. A glass, wherein: The glass contains, in mole percentage based on oxides: 52%~70% SiO2, 14% to 25% Al2O3, 10% to 18% Li2O, 1% to 7% Na2O, 0.1% to 5% K2O, and 0~0.8% ZrO2, The parameter M obtained by the following formula from the contents of SiO2, Al2O3, Li2O, Na2O, K2O, B2O3, P2O5, MgO, ZnO, ZrO2, and Y2O3 in mol % [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3] is 2 or more and 20 or less, The parameter D obtained by the following formula from [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3] is greater than 1200. D=-943×[SiO2]-859×[Al2O3]-998×[Li2O]-991×[Na2O]-1013×[K2O] -949×[B2O3]-941×[P2O5]-687×[MgO]-956×[ZnO]-1516×[ZrO2]-823×[Y2O3]+95174, M=-1.15×[SiO2]-1.73×[Al2O3]+0.155×[Li2O]+0.74×[Na2O]-4.75 ×[K2O]-2.1×[B2O3]-2.17×[P2O5]+3.25×[MgO]-2.0×[ZnO]-13.3×[ZrO2]-0.80×[Y2O3]+120, The S value represented by the following formula is 0.34 or less, S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K ) Here, P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O]) P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O]) P K =[K2O] / ([Li2O]+[Na2O]+[K2O]) Wherein, [Li2O], [Na2O], and [K2O] represent the contents of Li2O, Na2O, and K2O in molar percentage, respectively. When the glass having a thickness of 700 μm is immersed in NaNO3 at 380°C for 4 hours, the surface compressive stress value CS0(Na) generated is 500 MPa or more. When the glass having a thickness of 700 μm is immersed in KNO3 at 380°C for 4 hours, the surface compressive stress value CS0(K) generated is 1200 MPa or more. When the glass having a thickness of 700 μm is immersed in KNO3 at 380°C for 4 hours, the depth of the compressive stress layer DOL(K) generated is 3 μm or more, and The ratio DOL(Na) / DOL(K) of the depth of the compressive stress layer DOL(Na) generated when the glass having a thickness of 700 μm is immersed in NaNO 3 at 380° C. for 4 hours to the DOL(K) is 11.8 or less.

4. The glass according to claim 3, wherein: The compressive stress value CS at a depth of 50 μm from the surface generated when the glass having a thickness of 700 μm was immersed in NaNO3 at 380°C for 4 hours was 50 (Na) is 170 MPa or more.

5. The glass according to any one of claims 1 to 4, wherein: The devitrification temperature of the glass is 1350° C. or lower.

6. The glass according to any one of claims 1 to 4, wherein: The viscosity of the glass reaches 10 2 The temperature T2 at dPa·s is 1750°C or less.

7. The glass according to any one of claims 1 to 4, wherein: The temperature of the DSC exothermic peak measured by the following test method is 150°C or higher than the glass transition temperature. (Test method) 70 mg of glass was pulverized and ground with an agate mortar, and measured from room temperature to 1200° C. using a differential scanning calorimeter (DSC) at a heating rate of 10° C. / min.

8. A chemically strengthened glass, wherein the chemically strengthened glass is a chemically strengthened glass having a surface compressive stress value of 400 MPa or more, wherein: When the Na2O concentration distribution is obtained in the depth direction from the surface to the center of the plate thickness, the depth at which the Na2O concentration reaches the maximum is 1 μm or more, and The basic composition of the chemically strengthened glass comprises, in terms of molar percentage based on oxides: 52%~70% SiO2, 14% to 25% Al2O3, 10% to 18% Li2O, 1% to 7% Na2O, 0.1% to 5% K2O, and 0~0.8% ZrO2, The parameter M obtained by the following formula from the contents of SiO2, Al2O3, Li2O, Na2O, K2O, B2O3, P2O5, MgO, ZnO, ZrO2, and Y2O3 in mol % [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3] is 2 or more and 20 or less, The parameter D obtained by the following formula from [SiO2], [Al2O3], [Li2O], [Na2O], [K2O], [B2O3], [P2O5], [MgO], [ZnO], [ZrO2], and [Y2O3] is greater than 1200. D=-943×[SiO2]-859×[Al2O3]-998×[Li2O]-991×[Na2O]-1013×[K2O] -949×[B2O3]-941×[P2O5]-687×[MgO]-956×[ZnO]-1516×[ZrO2]-823×[Y2O3]+95174, M=-1.15×[SiO2]-1.73×[Al2O3]+0.155×[Li2O]+0.74×[Na2O]-4.75 ×[K2O]-2.1×[B2O3]-2.17×[P2O5]+3.25×[MgO]-2.0×[ZnO]-13.3×[ZrO2]-0.80×[Y2O3]+120, The S value represented by the following formula is 0.34 or less, S=-P Li ×log(P Li )-P Na ×log(P Na )-P K ×log(P K ) Here, P Li =[Li2O] / ([Li2O]+[Na2O]+[K2O]) P Na =[Na2O] / ([Li2O]+[Na2O]+[K2O]) P K =[K2O] / ([Li2O]+[Na2O]+[K2O]) Wherein, [Li2O], [Na2O], and [K2O] represent the contents of Li2O, Na2O, and K2O in molar percentage, respectively. The ratio DOL(Na) / DOL(K) of the compressive stress layer depth DOL(Na) generated when the glass with a thickness of 700 μm is immersed in NaNO3 at 380°C for 4 hours to the compressive stress layer depth DOL(K) generated when the glass with a thickness of 700 μm is immersed in KNO3 at 380°C for 4 hours is less than 11.

8.

9. The chemically strengthened glass according to claim 8, wherein: The compressive stress value CS of the chemically strengthened glass at a depth of 50 μm from the surface is 50 It is above 90MPa.

10. The chemically strengthened glass according to claim 8 or 9, wherein: The chemically strengthened glass has an internal tensile stress value CT of 70.6 MPa or less.

11. The chemically strengthened glass according to claim 8 or 9, wherein: The surface compressive stress value CS0 of the chemically strengthened glass is greater than or equal to 800 MPa.

12. The chemically strengthened glass according to claim 8 or 9, wherein: The frequency hopping of the chemically strengthened glass is 10 2.5 above.

Citation Information

Patent Citations

  • Chemically strengthened glass

    JP2013520388A

  • Glass with improved drop performance

    JP2019517985A

  • Information processing apparatus, information processing program and information processing system

    JP2020119445A

  • Strengthened glass with deep depth of compression

    US20150259244A1

  • Cover glass, and in-cell liquid crystal display device

    WO2019159981A1